x = 4 would be the solution of the given problem.
I can't speak to the first part of this question, as I don't totally have context for what they're asking, but we can solve for x using one of the laws of logarithms, namely:
log.m + log.n = log.mn
Using this law, we can combine and rewrite our initial equation as
log(x^2- x) = 3
Remember that logarithms are simply another way of writing exponents. The logarithm is just another way of writing the fact . Keeping that in mind, we can express our logarithm in terms of exponents as
log(x^2- x) = 3 --> x^2- 2x = 8
2³ = 8, so we can replace the left side of our equation with 8 to get
x^2 - 2x - 8 =0
(x-4)(x+2) = 0
Hence x = 4 0r -2. As x cannot be negative so it would be 4.
Learn more about Expression on:
brainly.com/question/1280754
#SPJ4